2020
DOI: 10.1016/j.immuni.2020.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Regulation via Nested Antagonistic Feedback Circuits Mediated by the Receptors CD28 and CTLA-4 Confers Robustness to T Cell Population Dynamics

Abstract: Highlights d T cell clusters are communication hubs for coordination of population dynamics d T cells can regulate their own population dynamics akin to quorum regulation d T cell quorum regulation incorporates two nested antagonistic feedback circuits d Loop dominance of feedback circuits is controlled by local T cell density

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 51 publications
(74 reference statements)
5
66
0
Order By: Relevance
“…In vivo, activated CD4 + T cells clustering around DCs cause CD8 + T cell accumulation through CCL3/CCL4-CCR5 binding, which enhances CD8 + T cell/DC contact formation [65], highlighting the crucial role of chemokines in enabling activating T cells to find each other and create the niche that serves as a platform for subsequent T-T communication. While this mechanism relies on another cellular intermediate, it is conceivable that T cells also directly attract each other via other chemokines, as they up-regulate multiple chemokine/chemokine receptor pairs [15].…”
Section: B-chemokinesmentioning
confidence: 99%
See 4 more Smart Citations
“…In vivo, activated CD4 + T cells clustering around DCs cause CD8 + T cell accumulation through CCL3/CCL4-CCR5 binding, which enhances CD8 + T cell/DC contact formation [65], highlighting the crucial role of chemokines in enabling activating T cells to find each other and create the niche that serves as a platform for subsequent T-T communication. While this mechanism relies on another cellular intermediate, it is conceivable that T cells also directly attract each other via other chemokines, as they up-regulate multiple chemokine/chemokine receptor pairs [15].…”
Section: B-chemokinesmentioning
confidence: 99%
“…Various studies have demonstrated that activated T cells are able to find each other [65,94,95]. Multiple chemokine/receptor pairs are upregulated by T cells following priming [15], suggesting that primed T cells can attract each other. Similarly, antigen-specific CD8 + T cells favour the priming of naive CD8 + T cells, by promoting the CCR5-dependent recruitment of polyclonal CD8 + T cells to mature dendritic cells [94], resulting in the amplification of priming.…”
Section: Regulation Of T Cell Primingmentioning
confidence: 99%
See 3 more Smart Citations